INTEGRATING WELLNESS: A CRITICAL EXAMINATION OF ALTERNATIVE MEDICINE’S IMPACT ON CONTEMPORARY HEALTHCARE - Mohammed Ali Alzamanan, Soud Ali Mohammad Alyami, Mahdi ali mohammed al yami, Hezam Abdullah Saud Alyami, Saleh Hamad Mana Al Murdif, Saleh ali mohammad alyami (Chelonian Research Foundation, 2023)
This comprehensive review critically examines the evolving role of alternative medicine within modern healthcare systems. Despite its growing popularity and integration into mainstream healthcare, alternative medicine remains a contentious topic, surrounded by debates over its efficacy, scientific validation, and safety. This article delves into the historical context of alternative therapies, their appeal to the public, and the scientific scrutiny they face. It explores the ethical and safety considerations of incorporating unproven treatments into patient care and the challenges of integrating alternative therapies with conventional medical practices. Through an analysis of patient experiences, clinical evidence, and future directions, this article aims to provide a balanced perspective on the potential benefits and limitations of alternative medicine in enhancing holistic wellness and patient-centered care in contemporary healthcare settings. Keywords: Alternative Medicine, Integrative Healthcare, Holistic Wellness, Complementary Therapies, Patient-Centered Care, Ethical Considerations, Safety of Alternative Therapies, Clinical Efficacy